The Security Council's Contribution to a Global Concept of the Rule of Law - Wieczorek, Nuscha (Schriftenreihe für internationales Recht (SIR), 2020)
Beginning in the 1990s, the concept of the rule of law has been increasingly invoked in UN Security Council resolutions. The Security Council applies the principle of the rule of law as an instrument to fulfil its core mandate of restoring and maintaining international peace and security. Taking account of the heterogeneous composition of the Council and its far-reaching competences, this monograph examines whether the UN body develops its own understanding of the rule of law, a principle strongly anchored in national constitutional law, or whether the invocation of the principle in its resolutions points to an emerging global understanding. For the examination of the function and partial guarantees of the rule of law in Security Council resolutions, the monograph undertakes a comparative study of all resolutions that explicitly mention the principle of the rule of law and thus analyses the phenomenon comprehensively. The monograph addresses the central question which role the United Nations and the UN Security Council can play in upholding the rule of law nationally and internationally.